Injury and fatality risks for child pedestrians and cyclists on public roads - David I. Swedler; Bina Ali; Rebecca Hoffman; Jennifer Leonardo; Eduardo Romano; Ted R. Miller (BMC, 2024)
Abstract Background Pedestrians and cyclists are often referred to as "vulnerable road users," yet most research is focused on fatal crashes. We used fatal and nonfatal crash data to examine risk factors (i.e., relationship to an intersection, urbanicity, crash circumstances, and vehicle type) for police-reported pedestrian and cyclist injuries on public roads among children aged 0-9 and aged 10-19. We also compared risk factors among these two age groups with adults aged 20-29 and aged 30-39. Methods Crash data were obtained for 2016-2020 from the National Highway Traffic Safety Administration's Fatality Analysis Reporting System for fatal crash injuries and Crash Report Sampling System for nonfatal crash injuries. We collected data on victim demographics, roadway, and vehicle- and driver-related factors. Descriptive analyses were conducted between and within pedestrian and cyclist victims. Results We analyzed 206,429 pedestrian injuries (36% in children aged 0-19) and 148,828 cyclist injuries (41% in children aged 0-19) from 2016 to 2020. Overall, child pedestrians had lower injury rates than adults, but children aged 10-19 had greater cycling crash rates than adults. Almost half of the pedestrian injuries in children aged 0-9 were "dart-out" injuries (43%). In the majority of the cyclist injuries, children in both age groups failed to yield to vehicles (aged 0-9 = 40% and aged 10-19 = 24%). For children and all ages included in the study, the fatality risk ratio was highest when pedestrians and cyclists were struck by larger vehicles, such as trucks and buses. Further exploration of roadway factors is presented across ages and transportation mode. Conclusion Our findings on child, driver, vehicle, and roadway factors related to fatal and nonfatal pedestrian and cyclist injuries may help to tailor prevention efforts for younger and older children.